University-Community Engagement in Malaysia:Practices and Prospects - Lee , Mei Ph'ng; Agus, Setyo Budi; Zolkepli, Buang; Norizan, Md Nor; Hassan, Naziri Khalid; Mohd Ridzuan, Nordin (The Ministry of Higher Education Malaysia, 2008)
Introduction